Analysis of Students’ Problem-Solving Skills and Learning Difficulties in Dynamic Fluid Topics through a Preliminary Study in Physics Education - Azrisa Mutia; Muhammad Minan Chusni (Alpatih Harapan Semesta, 2026)
This study examines a fundamental question: how students’ problem-solving skills develop and what difficulties they face in learning fluid dynamics. The research is positioned within physics education, focusing on the importance of conceptual understanding and problem-solving skills.A qualitative descriptive approach was applied using triangulation methods, including diagnostic tests, interviews, and classroom observations. The diagnostic test measured students’ ability to analyze problems and apply concepts, while interviews and observations explored learning difficulties and instructional practices.The results indicate that students’ problem-solving skills are low and mostly procedural. Students tend to rely on memorizing formulas rather than understanding concepts, leading to difficulties in solving contextual problems and relating key variables such as pressure, velocity, and height. Additionally, teacher-centered instruction limits students’ opportunities to think critically and solve problems independently.These findings suggest the need for more interactive and problem-based learning approaches to enhance students’ conceptual understanding and problem-solving skills in physics